Nucleotide Transport and Metabolism in Diatoms - Gruber, Ansgar (Biomolecules, 2019)
Plastids, organelles that evolved from cyanobacteria via endosymbiosis in eukaryotes, provide carbohydrates for the formation of biomass and for mitochondrial energy production to the cell. They generate their own energy in the form of the nucleotide adenosine triphosphate (ATP). However, plastids of non-photosynthetic tissues, or during the dark, depend on external supply of ATP. A dedicated antiporter that exchanges ATP against adenosine diphosphate (ADP) plus inorganic phosphate (Pi) takes over this function in most photosynthetic eukaryotes. Additional forms of such nucleotide transporters (NTTs), with deviating activities, are found in intracellular bacteria, and, surprisingly, also in diatoms, a group of algae that acquired their plastids from other eukaryotes via one (or even several) additional endosymbioses compared to algae with primary plastids and higher plants. In this review, we summarize what is known about the nucleotide synthesis and transport pathways in diatom cells, and discuss the evolutionary implications of the presence of the additional NTTs in diatoms, as well as their applications in biotechnology.